Steam activation tuned porous structure and surface wetting behaviors of mesoporous biochars for corrosive oily wastewater treatments. Issue 8 (5th May 2022) - Gao, Yuqing; Hao, Baicun; Xue, Ni; Wang, Yujia; Xiao, Hanzhong; Huang, Xin; Shi, Bi
Abstract: BACKGROUND: Oil pollution has drawn a great deal of attention due to the large quantity of oily wastewater generated from various industries. Some industrial processes discharge corrosive oily wastewater that is difficult to be separated by conventional approaches. Moreover, the co‐existence of oil pollution with other pollutants further increases the separation difficulty of oily wastewater. RESULTS: Herein, distillers' grains (DG) were utilized as raw materials to prepare mesoporous biochars and further tuned their structure and surface wetting behaviors by steam activation, which improved the contacts between the DG biochars and the oil‐in‐water (O/W) emulsion droplets for demulsification as well as the volumetric capacity for oil capture. The as‐prepared DG biochars realized a highly efficient separation of corrosive O/W nanoemulsions with the separation efficiency high up to 99.9996%. Moreover, the DG biochars separated dye‐containing corrosive O/W emulsions with ~100% removal of dyes and obtained a separation efficiency of corrosive O/W emulsions high up to 99.9981%. CONCLUSION: We have explored an effective approach for developing mesoporous DG biochars, with tunable pore structure and surface wetting properties, that are highly efficient for separating corrosive O/W emulsions. The present investigation not only provides a useful approach for remedying the contamination caused by corrosive oily wastewater but it also develops a new route for realizing value‐added utilization of solid wastes generated by the distilled liquor industry. © 2022 Society of Chemical Industry (SCI).